The reliability of assessment of oestrogen receptor expression on needle core biopsy specimens of invasive carcinomas of the breast. Issue 3 (26th May 2006) - Hodi, Zsolt; Chakrabarti, Jayeta; Lee, Andrew H S; Ronan, John E; Elston, Christopher W; Leung Cheung, Kwok; Robertson, John F R; Ellis, Ian O
Abstract : Aim: To assess the reliability of assessment of oestrogen receptor expression on needle core biopsy specimens of invasive carcinomas of the breast. Previous studies have mostly been small, with a range of agreement from 62% to 100%. Methods: Retrospective audit of 338 tumours surgically excised within 60 days of core biopsy, that had had oestrogen receptor assessed on both the core biopsy and tumour specimens. Surgical specimens were incised when fresh to ensure good fixation. External controls including a weakly positive tumour were included in each immunohistochemistry run. Results: Oestrogen receptor expression was bimodal, with H score in both specimens of either 0 or >50 in 96% of tumours. Using H score cut-off of 10 for positivity, there was an agreement between core and excision in 334 of 338 tumours (98.8%). All discrepancies were between weakly positive and negative tumours. Intratumoral heterogeneity could explain the one tumour that was negative on core and positive on excision. H score tended to be slightly higher on core than excision (means 146 and 136). Better fixation on the core is the most likely explanation for this and for the three tumours that were positive on core and negative on excision. Repeat staining on tumours with discrepant results gave similar results in all except one case. An internal control was present in 97% of excisions and 55% of cores of oestrogen receptor-negative tumours; the internal control stained positively in all except two sections. Conclusion: Oestrogen receptor can be assessed reliably on needle core biopsies of invasive carcinomas of the breast.